LRINEC Scoring Accuracy and Its Association with Clinical Outcomes in Necrotizing Fasciitis Patients - Ronald Ronald; Teguh Marfen Djajakusumah; Rani Septrina (Majalah Kedokteran Bandung, 2026)
Necrotizing Fasciitis (NF) is a soft tissue infection characterized by rapidly progressive necrosis of the fascia and is associated with high morbidity and mortality worldwide. It has atypical clinical symptoms during the early course of the disease, making timely diagnosis challenging. Early and adequate antibiotic therapy combined with timely surgical intervention is essential to reduce morbidity and mortality in NF. Consequently, realiable diagnostic tools are needed for early diagnosis of NF. The LRINEC score is one of the diagnostic tools that is simple and rapidly applicebe; however, its use in diagnosing NF is still under debate. This study aimed to determine the accuracy of LRINEC scoring in diagnosing NF compared to histopathological examination (the gold standard) and to assess its association with morbidity and mortality. This observational prospective cohort study included NF patients presenting to the surgical emergency department throughout 2024. A total of 29 patients were enrolled, with an average age of 53.9 years, dominated by men. Diabetes mellitus was the most common comorbidity, present in 18 patients (72.9%). Death occurred in 1 patient (3.4%). The mean LRINEC score among subjects was 6.3. The LRINEC score demonstrated an accuracy of 89.66% compared to histopathological findings, with a sensitivity of 95% and a specificity of 77.78% for scores >6. Thus, thee LRINEC score demonstrates good diagnostic accuracy for necrotizing fasciitis, despite the lack of statistically significant association between LRINEC score and morbidity or mortality in this study.